Pre-mRNA processing factors differentially impact coordination between co-transcriptional cleavage and transcription termination - Xianhao Jin; Juzuo Li; Wenqin Lu; Xian Deng; Yanping Wei; Yi Shu; Bo Liu; Zhijian Liu; Yanping Long; Xinlong Zhu; Qili Fei; Yiji Xia; et al. (Nature Communications)
Abstract Co-transcriptional cleavage and transcription termination are closely related processes during mRNA maturation, yet their coordination remains poorly understood due to difficulties in detecting these transient events. Here, we applied single-molecule nascent RNA sequencing to simultaneously capture the cleavage status and readthrough distance on the same nascent RNA molecules and characterize 14 mutants of various pre-mRNA processing factors in Arabidopsis. Our results reveal diverse roles for these processing factors in coordinating cleavage and termination: core components of CPSF and CstF complex stimulate both cleavage and termination, facilitating access to exoribonuclease AtXRN3; mutations in nuclear poly(A) polymerase PAPS1 and AtXRN3 caused delayed termination with minimal effects on cleavage, suggesting their roles are further downstream; BORDER proteins facilitate termination while simultaneously inhibiting cleavage, suggesting a complex interplay between these two actions; the phosphatase SSU72 specifically promotes efficient termination without affecting cleavage. Our method also enables us to distinguish cleaved readthrough transcripts from full-length readthrough, and we found termination factor FPA specifically promotes termination of cleaved readthrough, suggesting FPA facilitates access of AtXRN3 to the 3’ cleavage product. Our comprehensive datasets reveal cleavage and termination are highly coordinated during pre-mRNA processing.